Exhibit labels an interpretive approach - Serrell, Beverly 1943-; Whitney, Katherine 1962- (Lanham, Maryland Rowman & Littlefield Publishers, 2024)
This guide to writing interpretive exhibit labels is updated to include new voices, current scholarship and the unique issues the museum field is grappling with in the 21st century. This edition is more accessible and easier to use for all museum professionals, from label writers to museum directors to exhibit designers"-- Provided by publisher.
Keywords: Museums labels -- Handbooks, manuals, etc; Museum techniques -- Handbooks, manuals, etc